The influence of stigma and discrimination on female sex workers' access to HIV services in St. Petersburg, Russia. - King, Elizabeth J; Maman, Suzanne; Bowling, J Michael; Moracco, Kathryn E; Dudina, Viktoria (AIDS and behavior, 2013)
Stigma associated with HIV and risk behaviors is known to be a barrier to health care access for many populations. Less is known about female sex workers (FSW) in Russia, a population that is especially vulnerable to HIV-infection, and yet hard-to-reach for service providers. We administered a questionnaire to 139 FSW to better understand how stigma and discrimination influence HIV service utilization. Logistic regression analysis indicated that HIV-related stigma is negatively associated with uptake of HIV testing, while sex work-related stigma is positively associated with HIV testing. HIV-positive FSW are more likely than HIV-negative FSW to experience discrimination in health care settings. While decreasing societal stigma should be a long-term goal, programs that foster inclusion of marginalized populations in Russian health care settings are urgently needed.
Keywords: Adult; Cross-Sectional Studies; Female; Health Services Accessibility; Health Services Needs and Demand; Health Status Disparities; HIV Seropositivity; Humans; Prejudice; Prostitution; Questionnaires; Risk-Taking; Russia; Sex Workers; Sexual Behavior; Social Perception; Social Stigma